Directions of adaptation of Ukrainian commercial enterprises to the challenges of war - Tsymbalenk, Nataliia; Tarasenko, Oleksii (Herald of Economics, 2025)
Introduction. The current operating conditions of trade enterprises in Ukraine are characterized by large-scale external challenges and threats, among which military actions have become the decisive factor. The war has caused significant economic losses due to infrastructure damage, disruptions in supply chains, reduced consumer demand, and growing financial risks. At the same time, business entities in the trade sector have demonstrated flexibility by accelerating digitalization, diversifying supply chains, and utilizing national and international financial support mechanisms. The purpose of the study is to systematize the main directions of adaptation to the consequences of the war by domestic trade enterprises, based on the analysis of trade development trends in Ukraine. Research methods. The study applies methods of comparison and grouping to systematize and generalize research results, as well as statistical methods of analysis and graphical presentation of time series. The factual basis was formed using official data from the State Statistics Service of Ukraine and international analytical reports. Results. Based on the analysis of the dynamics of wholesale and retail trade turnover in Ukraine during 2011–2025, a general upward trend was identified, which indicates a high level of adaptability among enterprises. It was substantiated that the main directions of adaptation of Ukrainian trade enterprises to wartime challenges should include business relocation, asset conservation, digitalization, improvement of trade personnel management, diversification of sales markets and supply chains, adjustment of product assortment policies, and investments in security and energy resilience. Conclusions. Despite the unprecedented challenges of the war, trade enterprises in Ukraine have managed to ensure a gradual recovery of their operations. The main factors of resilience were digitalization, organizational flexibility, the use of financial support, and the reorientation of business models. At the same time, systemic risks require further coordinated actions by the state, business, and international partners. Prospects. Further research should focus on analyzing the impact of international financial support on the structural transformation of Ukraine’s trade sector, as well as on developing sustainable development models for trade enterprises in the post-war period, taking into account systemic risks and current trends in the evolution of trade entrepreneurship in Ukraine.